PANDANGAN ULAMA TENTANG ZAKAT PROFESI - Pakpahan, Elpianti Sahara (Lembaga Jurnal dan Seminar Universitas Pembangunan Panca Budi, 2018)
Zakat is a pillar of Islam that has an Islamic socio-economic character. Therefore the scholars of fiqih spill his attention by discussing the zakat profession. The fiqh scholars interpret the verse verses related to zakat, such as surah Al-Baqarah: 267, surah at-Taubah: 34, 60, and 103 and other verses. Zakat profession is not known at the time of the Prophet SAW. Zakat profession is the ijtihad of the scholars of today who depart from ijtihad that has enough basis and a strong reason. Among the contemporary scholars who argue the existence of professional zakat is Shaykh Abdur Rahman Hasan, Sheikh Muhammad Abu Zahrah, Sheikh Abdul Wahab Khalaf and Shaykh Yusuf Qardhawi. They argue that all income through professional activities such as physicians, consultants, artists, accountants, notaries, etc., when it reaches nishab, it is obligatory to pay zakat.